A quasi real-time approach to investigating the damage and fracture process in plain concrete by X-ray tomography - Yuan, Qin; Junrui, Chai; Weihua, Ding; Faning, Dang; Man, Lei; Zengguang, Xu (Journal of Civil Engineering and Management, 2016)
In most concrete-related computer tomography (CT) experiments, detailed information on the damage and fracture process is obtained using nonreal-time approaches, with the CT method constantly regarded as a qualitative method. This study develops a quasi real-time method with the use of experimental instruments. The average CT number is used to analyse the damage and fracture process in concrete specimens and the theory that underlies concrete damage and fracture is improved. Various characteristics of the fracture form in different loading cases are investigated at the macro and micro levels. This study provides a convenient and fast method for qualitatively and quantitatively analysing concrete. First published online: 01 Jun 2015